Data sense-making and communicative gaps on sundhed.dk - Mahnke, Martina Skrubbeltrang; Petersen, Matilde Lykkebo; Nielsen, Mikka (MedieKultur: Journal of media and communication research, 2023)
This paper examines personal experiences of digital health data on the Danish eHealth platform sundhed.dk. Taking a patient’s view, the paper understands data sense-making as an embodied communicative practice. The empirical analysis, consisting of 24 purposefully sampled interviews, is brought together with the conceptual framework describing and unpacking the ambivalences to be found in digital health data experiences into themes of data ambivalence, emotional ambivalence, communicative ambivalence and identity ambivalence. This in-depth empirical description of patients’ ambivalent experiences contributes to a more nuanced understanding of the profound changes digital health data is having on a patients’ everyday lives. In particular, it emphasizes the communicative challenges arising from the constant availability of digital health data anytime, anywhere, and calls for further research into the new and unfamiliar communicative situations in which patients are placed and forced to navigate in.